Using super capacitors to interface a small wind turbine to a grid-tied micro-inverter - Eldridge, Christopher Sean (Kansas State University, 2011)
During the development of an educational renewable energy production platform, it was found that there were no low-cost, efficient grid-tie interfaces for a 160 W DC wind turbine. Typically, a small DC wind turbine is used in conjunction with a rechargeable battery bank or, if the wind turbine is directly interfaced with a grid-tie inverter, a regulator with a diversion-load. The use of batteries is undesirable due to their high-cost and high-maintenance characteristics. Diversion loads by nature waste power, as any excess energy that cannot be accepted by a battery or inverter is usually converted into heat through a resistive element. Initially, a 24 V DC, 160 W Air Breeze small wind turbine was directly connected to an Enphase Energy M190 grid-tie micro-inverter. The 24 V DC Air Breeze wind turbine is designed to charge a battery or bank of batteries while the M190 micro-inverter is designed to convert the DC output of a 200 W solar panel to grid-tied AC power. As expected, the power-production response time associated with the small wind turbine and the power-accepting, load-matching response time of the micro-inverter were not compatible. The rapidly changing power output of the small wind turbine conflicted with the slow response time of the micro-inverter resulting in little power production. Ultimately, the response time mismatch also produced sufficiently large voltage spikes to damage the turbine electronics. In this thesis, a solution for a low-cost, efficient grid-tie interface using no batteries and no diversion load is presented. A capacitance of eight Farads is placed in parallel with the small wind turbine and the micro inverter. The large capacitance sufficiently smoothes the potential abrupt voltage changes produced by the wind turbine, allowing the micro-inverter adequate time to adjust its load for optimal power conversion. Laboratory experiments and data from an implementation of such a parallel super capacitor wind turbine to grid-tie micro-inverter configuration are provided along with DC and AC power production monitoring circuits interfaced with a micro controller.
Keywords: Super capacitor; Small wind turbine; Micro inverter; Grid tie; Electrical Engineering (0544)